Intermediate metabolites of the pyrimidine metabolism pathway extend the lifespan of C. elegans through regulating reproductive signals - Wan, Qin-Li (Aging (Albany NY), 2019)
The pyrimidine metabolism pathway has important biological functions; it not only maintains appropriate pyrimidine pools but also produces bioactive intermediate metabolites. In a previous study, we identified that the pyrimidine metabolism pathway is associated with aging regulation. However, the molecular mechanism by which the pyrimidine metabolism pathway regulates aging remains unclear. Here, we investigated the longevity effect of pyrimidine intermediates on Caenorhabditis elegans (C. elegans). Our results demonstrated that the supplementation of some pyrimidine intermediates could extend the lifespan of C. elegans. In addition, the RNAi knockdown of essential enzymes involved in pyrimidine metabolism could also significantly affect lifespan. We further investigated the molecular mechanism by which a representative intermediate metabolite, thymine, extends the lifespan of worms and found that thymine-induced longevity required the nuclear receptors DAF-12 and NHR-49, and the transcription factor DAF-16/FOXO. Further pathway analysis revealed that the longevity effect of thymine depended on the inhibition of reproductive signals. Additionally, we found that other pyrimidine intermediates functioned in a manner similar to thymine to prolong lifespan in C. elegans. Taken together, our results revealed that pyrimidine intermediates increased lifespan by inhibiting reproductive signals and subsequently inducing the function of DAF-12, NHR-49 and DAF-16 in C. elegans.